PERHITUNGAN BEBAN PENDINGINAN INSTALASI TATA UDARA SISTEM FAN COIL CHILLED WATER DI GEDUNG SHOWROOM MOBIL JAKARTA - Andri Setiawan; Joko Prihartono; Purwo Subekti (Jurnal APTEK, 2014)
Air conditioning for the building to be used as a car showroom in Jakarta is one thing that is needed to provide comfort and freshness to the workers so that the quality and quantity of work produced optimal . The cooling load can be influenced by various factors , among others : the weather , the condition of the building , the building volume , the shape of the building structure and the building materials used , the amount of ventilation air required , the function of the building , number of occupants , condition the outside air , indoor air conditions .